The effect of Ce content on structure and stability of Gd1-xCexPO4: Theory and experiment. Issue 4 (April 2019) - Zhao, Xiaofeng; Li, Yuxiang; Teng, Yuancheng; Wu, Lang; Bi, Peng; Yang, Xiaoyong; Wan, Lili
Abstract: The structure distortion, bonding character, defect stability and chemical stability of Gd1- x Ce x PO4 ( x = 0, 0.25, 0.5, 0.75 and 1) have been investigated by combined with experimental and first principles calculations to understand the effect simulate actinides on the structural stability of Gd-monazite. The result shows that the Gd1- x Ce x PO4 ( x = 0–1) ceramics could be prepared at 1450 °C, and Ce 3+ is easily incorporated into Gd-monazite lattice. The structural analysis indicates that the symmetry of [GdO9 ] polyhedron decreases with increasing Ce content. The evolution of Gd defect stability and chemical stability in Gd1- x Ce x PO4 ( x = 0–1) is tightly associated with the distortion of [GdO9 ] polyhedron, in which a greater distortion will induce more unstable. The best chemical stability in pH = 3 and 11 leachates is CePO4, followed by GdPO4, Gd0.75 Ce0.25 PO4, Gd0.5 Ce0.5 PO4, and finally Gd0.25 Ce0.75 PO4, revealing the GdPO4 monazite is perfectly suitable to immobilize actinides with relative low dose ratio.